PUF60: a prominent new target of the autoimmune response in dermatomyositis and Sjögren's syndrome. Issue 6 (7th August 2015) - Fiorentino, David F; Presby, Matthew; Baer, Alan N; Petri, Michelle; Rieger, Kerri E; Soloski, Mark; Rosen, Antony; Mammen, Andrew L; Christopher-Stine, Lisa; Casciola-Rosen, Livia
Abstract : Objectives: Autoantibodies are used clinically to phenotype and subset patients with autoimmune rheumatic diseases. We detected a novel 60 kDa autoantibody specificity by immunoblotting using a dermatomyositis (DM) patient's serum. Our objective was to identify the targeted autoantigen and to evaluate disease specificity and clinical significance of this new autoantibody. Methods: A new 60 kDa specificity was detected by immunoblotting HeLa cell lysates. The targeted autoantigen was identified as poly(U)-binding-splicing factor 60 kDa (PUF60) using (i) a human protein array and (ii) two-dimensional gel electrophoresis and liquid chromatography tandem mass spectrometry peptide sequencing. Anti-PUF60 antibodies were assayed by ELISA using sera from patients with primary Sjögren's syndrome (SS; n=84), systemic lupus erythematosus (SLE; n=71), DM (n=267), polymyositis (n=45), inclusion body myositis (n=45) and healthy controls (n=38). Results: PUF60 was identified as a new autoantigen. Anti-PUF60 antibodies were present in 25/84 (30%) patients with SS, 6/71 (8.5%) patients with SLE and 2/38 (5.0%) control subjects (SS vs controls, p=0.002; SLE vs controls, p=0.711). Anti-PUF60 antibodies were present in 48/267 (18.0%) patients with DM versus 4/45 (8.9%) and 5/45 (11.1%) patients with inclusion body myositis and polymyositis, respectively. The antibody was significantly associated with anti-Ro52 antibodies, rheumatoid factor and hyperglobulinemia in the patients with primary SS. In patients with DM, the antibody was associated with anti-transcription intermediary factor 1 gamma seropositivity and Caucasian race. Conclusions: PUF60 represents a novel autoantigen in patients with SS and DM. PUF60 antibodies are associated with distinct clinical features and different immune responses in different diseases.